KINEMATICS CHARACTERISTICS AND MODELING METHOD OF GANTRY PARALLEL STRUCTURE - XU HuiXing (Jixie qiangdu)
The kinematics of parallel structures in machine tool play an important role in the machining precision,and this paper focused on the kinematics and modeling of gantry parallel structure to analyze the dynamic response performance of the structure. It took a gantry parallel structure with plane motion for example,decomposed the motions of parallel structure with parallelogram,gave a gantry kinematic model of the system. Motion control method was studied to establish a projection function of model by the inputs and output. Based on this,the optimization algorithm was proposed to obtain the optimal control parameters for parallel structure,and the method can greatly improve the quick response of the parallel structure.